TV novel and the problems of Iraqi society: (The hostel) as a model - Jabara, Kawthar Mohammed Ali (Al-Adab Journal, 2019)
Within the Ramadan season in which the TV channels compete in presenting the latest and best programs and artworks produced throughout the previous year. The television work (The hotel), which was classified by its writer as a “TV novel", entered the Iraqi drama race, and this sparked a lot of controversy in the cultural and artistic circles as well as among viewers of different cultural levels. The attitudes were divided between those who issued judgments and those who expressed their opinion since the first and second episodes, not agreeing on a single opinion but starting from different technical, moral and political points of view. They were divided over the work between two situations angry and objecting or encouraging and praising, while a part of viewers contented with the follow-up until the work settles waiting for its end to issue the final judgment and say their opinion, including the author of this study. How does this artwork relate to well-known Narrative literature? Why was it called TV novel and not a drama or TV series as usual? What are the things that brought this work to the readable texts and what are the problems this work committed technically and intellectually?. In this study, we try to reach answers to all these questions by highlighting a set of issues that we will address in succession in several axes, namely: The first axis (the hotel and the novel), we discuss the relationship of (the hotel) with Narrative works first in terms of Genres and Secondly, in terms of his relationship with the Narrative work (Spiders of Avo), which is said to have been quoted. In the second axis: we touch on the idea of ​​the hotel and break the horizon of expectations and suspense techniques adopted by the work in building the event. In the third axis: we identify the issues raised by the episode, and in the fourth axis we discuss the character building and dialogue as one of its attachments between the text and performance, while the fifth axis is concerned with the narrator and the point of view that presented the television work under study, and the last axis deals with the artistic and intellectual errors of the episode. The research reached a number of results related to the literary Genres of the work and its technical and intellectual messages.